Effect of High Hydrostatic Pressure Processing on the Microbiological Quality and Bacterial Diversity of Sous-Vide-Cooked Cod - Diego Pérez Alcalá; María José Grande Burgos; Javier Rodríguez López; Rosario Lucas; Antonio Gálvez; Rubén Pérez Pulido (Foods, 2023)
High hydrostatic pressure (HP) is a promising method to improve the microbiological quality of sous-vide foods. Monitoring the composition and behavior of the microbial communities in foods is of most importance for the production of high-quality and safe products. High-throughput sequencing (HTS) provides advanced approaches to determine food’s microbial community composition and structure. The aim of the present study was to determine the impact of different HP treatments on the microbial load and bacterial diversity of sous-vide Atlantic cod. Sous-vide cooking at 57.1 °C for 30 min followed by HP treatment at 500 MPa for 8 min reduced viable cell counts (total aerobic mesophiles) in the cod samples below detectable levels for 45 days of storage under refrigeration. In a second trial with cod cooked sous-vide at 52 °C for 20 min followed by HP treatments at 300 or 600 MPa (with HP treatment temperatures of 22 °C or 50 °C for 4 or 8 min, depending on treatment), only the treatments at 600 MPa delayed bacterial growth for at least 30 days under refrigeration. The optimal HP conditions to improve the microbiological quality of sous-vide cod cooked at low temperatures were obtained at 600 MPa for 4 min at a pressurization temperature of 50 °C. Bacterial diversity was studied in cod cooked sous-vide at 52 °C for 20 min by HTS. In the absence of HP treatment, Proteobacteria was the main bacterial group. A succession of Pseudomonadaceae (Pseudomonas) and Enterobacteriaceae was observed during storage. Firmicutes had low relative abundances and were represented mainly by Anoxybacillus (early storage) and Carnobacterium (late storage). The HP-treated sous-vide cod showed the greatest differences from controls during late storage, with Aerococcus and Enterococcus as predominant groups (depending on the HP conditions). The application of HTS provided new insights on the diversity and dynamics of the bacterial communities of sous-vide cod, revealing the presence of bacterial genera not previously described in this food, such as Anoxybacillus. The significance of Anoxybacillus as a contaminant of seafoods should be further investigated.